THE SYNTHESIS AND PHYSICO-CHEMICAL PROPERTIES OF NANOSIZED TITANIUM DIOXIDE - KOVALENKO, IRYNA; POTASKALOV, VADYM; VLASENKO, NATALIYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents the study of synthesis nanodispersed titanium dioxide in a molten sodium and potassium nitrate medium with the addition of ammonium hydrofluoride as a titanium surface activator. It was found that by regulating the acid-base properties of the reaction medium, oxide materials with a data composition, degree of dispersion, and morphology can be obtained. Equimolar amounts of potassium and sodium nitrates, with a 10 wt.% excess relative to the stoichiometric requirements of the reaction, were employed. Ammonium hydrofluoride (NH₄F·HF) was used as an activating agent for the titanium surface. It was shown that with low “acidity” of the melt, TiO2 and polytitanate nanofibers with a diameter of 10–20 nm and a length of 250–350 nm are formed, and with increasing “acidity” of the medium, TiO2 nanocrystals with sizes of 30–50 nm are formed. The influence of nanoscale titanium dioxide on the electrical conductivity of a salt system in the solid and liquid states has been investigated. The possibility of using this solid-phase dielectric nanomaterial as an effective filler for increasing the electrical conductivity of ionic systems has been examined. A significant difference was found between the increase in electrical conductivity when filled with nanosized and microsized titanium dioxide. At a temperature of 170°C, the effect in two orders of magnitude stronger when using nano-TiO₂ in lithium-potassiumacetate eutectic. The fundamental feasibility of employing a solid-phase dielectric nanomaterial as a filler in ionic liquids to enhance their electrical conductivity was demonstrated. .The physicochemical properties, such composite systems should be considered as functional materials for the creation of energy conversion devices for a wide range of applications.